From Baseline to Recovery: An Audit of Pre- and Post-ECT (Electro Convulsive Therapy) Patient Assessments - Saba Ansari; Sujatha Maiya (BJPsych Open)
Aims: The audit was conducted to evaluate the effectiveness and procedural compliance of pre- and post-Electroconvulsive Therapy (ECT) assessments in accordance with the Scottish Electroconvulsive Therapy Accreditation Network (SEAN) Standard. Specifically, it assessed whether healthcare professionals are adhering to protocols by conducting the required Montreal Cognitive Assessment (MoCA), Montgomery–Åsberg Depression Rating Scale (MADRS), and Clinical Global Impression (CGI) evaluations. The goal is to enhance patient care and ensure strict adherence to established SEAN standards.